2018
DOI: 10.1097/brs.0000000000002493
|View full text |Cite
|
Sign up to set email alerts
|

Facet Sagittal Orientation

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The association between facet orientation and DLSS has been recently mentioned by Liu and colleagues who reported that individuals with DLSS had remarkable sagittal lumbar facet orientation (from L2-3 to L5-S1) compared with the control group [ 27 ]. Moreover, one study has shown that patients with sagittally oriented facets have narrow osseous spinal canals [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between facet orientation and DLSS has been recently mentioned by Liu and colleagues who reported that individuals with DLSS had remarkable sagittal lumbar facet orientation (from L2-3 to L5-S1) compared with the control group [ 27 ]. Moreover, one study has shown that patients with sagittally oriented facets have narrow osseous spinal canals [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Others, however, have disputed some of these associations [ 6 , 25 , 26 ]. Although one study [ 27 ] has recently reported that DLSS population manifested significantly smaller facet orientations compared to control yet, no study has investigated, to date, whether facet asymmetry can affect DLSS.…”
Section: Introductionmentioning
confidence: 99%
“…They protect the disk from excessive shear and rotation, whilst guiding motion between two adjacent vertebrae 30. An association between sagittal orientation of the lumbar facet joints and LDS have been proposed by previous studies 6,14,31–33. According to Boden et al 14 the threshold for sagittal oriented lumbar facet joints are 45° at L4/L5.…”
Section: Discussionmentioning
confidence: 88%
“…30 An association between sagittal orientation of the lumbar facet joints and LDS have been proposed by previous studies. 6,14,[31][32][33] According to Boden et al 14 the threshold for sagittal oriented lumbar facet joints are 45°at L4/L5. We confirm that sagittal oriented facet joints are predictive of radiographic instability.…”
Section: Facet Joint Anglementioning
confidence: 99%
“…Such dynamic effects on the lumbar spinal canal with axially loaded spine observed with computed tomography–myelography and MRI in patients with sciatica have been reported and agree to the findings of this study involving asymptomatic individuals [ 6 , 11 ]. These increments could also reflect increasing curvature of the lumbar spine, particularly at the thoracolumbar and lumbosacral junctions with the upright spine [ 18 21 ]. Reductions in disk heights reflect axial loading, though the reductions are not proportionately as large as reported in some earlier studies [ 22 24 ].…”
Section: Discussionmentioning
confidence: 99%